Effects of Different Urinary Catheterization Practices on Urinary Complications and Quality of Life - Yeliz Çulha; Funda Büyükyılmaz; Mehmet Gökhan Çulha (The New Journal of Urology)
Objective: This study investigates the effects of different urinary catheterization methods— transurethral catheterization (TC), suprapubic catheterization (SC), and clean intermittent catheterization (CIC)—on urinary complications and quality of life. Material and Methods: This research conducted as a descriptive design with 91 patients at a urology clinic in Istanbul between November 2023 and September 2024, the research evaluates catheterization-related complications and their impact on patients’ emotional, social, and physical well-being over a six-month period. Data collection utilized the Patient Information Form and the King’s Quality of Life Questionnaire. Results: Indicate that while all methods present complications such as urinary tract infections (UTIs), urgency, and hematuria, CIC and SC showed significant reductions in UTI rates over time (p=0.001 and p=0.042, respectively). CIC also resulted in fewer cases of hematuria compared to other methods (p=0.039). In terms of quality of life, SC demonstrated improvements in emotional and social domains over six months, whereas CIC offered enhanced autonomy and better physical health outcomes. Transurethral catheterization, despite its widespread use, was associated with higher complication rates, particularly UTIs. Conclusion: The findings underscore the importance of individualized catheterization decisions as based on multidisciplinary team approach and emphasize the critical role of nursing in following patient outcomes. Comprehensive patient education and adherence to hygiene protocols were instrumental in reducing complications and enhancing quality of life. Future studies should explore the long-term implications of these catheterization methods and further assess the role of nursing interventions in improving patient care.